Menggali potensi ekonomi melalui inovasi teknologi - Rohman, Danil Hairul (Maliki Interdisciplinary Journal, 2024)
In this article, the important role of technological innovation in driving global economic growth is highlighted. By exploring the concept, impact, challenges and opportunities of technological innovation, this paper illustrates how technology is shaping the modern economic landscape and providing enormous benefits in terms of efficiency, productivity, job creation and wealth distribution. By discussing the definition of technological innovation, its role in the economic context, and its impact on company performance and societal welfare, this article provides a comprehensive understanding of the complex relationship between technology and economic growth.